New oligonucleotide derivatives as unreactive substrate analogues and potential inhibitors of human apurinic/apyrimidinic endonuclease APE. Issue 1 (9th November 2015) - Kuznetsov, Nikita A.; Kupryushkin, Maxim S.; Abramova, Tatyana V.; Kuznetsova, Alexandra A.; Miroshnikova, Anastasia D.; Stetsenko, Dmitry A.; Pyshnyi, Dmitrii V.; Fedorova, Olga S.
Abstract : Human apurinic/apyrimidinic endonuclease APE1 is one of the key enzymes of the base excision DNA repair system. Abstract : Human apurinic/apyrimidinic endonuclease APE1 is one of the key enzymes of the base excision DNA repair system. The main biological function of APE1 is the hydrolysis of the phosphodiester bond on the 5′-side of an apurinic/apyrimidinic site (AP-site) to give the 5′-phosphate and 3′-hydroxyl group. It has long been known that AP-sites have mutagenic and cytotoxic effects and their accumulation in DNA is a potential hazard to the cell lifecycle. The structural and biochemical studies of APE1 are complicated by its high catalytic activity towards the AP-site and its cyclic or acyclic analogues. This work has focussed on the design, synthesis and analysis of oligonucleotide derivatives as potentially unreactive APE1 substrates. We have shown that the replacement of oxygen atoms in the phosphate group on the 5′-side from the AP-site analogue tetrahydrofuran (F) considerably decreases the rate of enzymatic hydrolysis of modified oligonucleotides. We have calculated that a N3′–P5′ phosphoramidate linkage is hydrolysed about 30 times slower than the native phosphodiester bond while phosphorothioate or primary phosphoramidate linkages are cleaved more than three orders of magnitude slower. The value of IC50 of the oligonucleotide duplex containing a primary phosphoramidate linkage is 2.5 × 10 −7 M, which is in accordance with the APE1 association constant of DNA duplexes containing AP-sites. Thus, it is demonstrated that oligonucleotide duplexes with chemical modifications could be used as unreactive substrates and potential competitive inhibitors of APE1.